ANALISIS EFEKTIVITAS IRIGASI AIR TANAH DI DESA ASOLU KECAMATAN ABUKI KABUPATEN KONAWE - Haydir, Haydir (Aksara Public, 2019)
Water is a very important natural resource for human life, therefore it is proper that these resources should be utilized and controlled to the maximum extent possible so that the potential contained in them is useful for life. Water resources can come from rainwater, surface water (rivers, lakes), springs, and ground water.Irrigation area in Asolu village, Abuki sub-district, Konawe district with 45 ha area is rain-fed rice field assisted by ground water irrigation in dry season. The purpose of this research is to study the irrigation water needs of paddy field and the level of effectiveness of groundwater irrigation in Asolu Village, Abuki District, Konawe District. Based on climatology data analysis using penman modification method, and effective rainfall calculation, the value of water demand (NFR) of 0,0484 m3 / sec, with the width of rice field area is 45 ha, and the availability of the groundwater irrigation (Q) in the village of Asolu is obtained at 0.0553 m3 / sec, thus it can be said that groundwater irrigation meets the water requirement for wetland rice farming in Asolu Village Abuki Sub-district of Konawe Regency. soil irrigation can be said to be effective because the discharge that is available on well I and well II is bigger than the water requirement in the rice field